The Impact of Celebrity Endorsement on Consumer’s Purchase Intention - Sucia Majid; Muhammad Sholahuddin; Soepatin Soepatin; Rini Kuswati (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2023)
Celebrity endorsement is a marketing strategy used by companies that involves celebrities and famous people or intellectuals who use their social status and reputation in society. It helps company to promote the product or service to consumer. They are not just to promote but to educate the consumer as well. It is mean to increase the product awareness. In addition, to that multinational corporations are used celebrity endorsement in their advertisement because of they strongly believed that the celebrities in advertisement have a unique vital such as they could attract and it create more influence on consumer buying behaviour, purchase intention and their brand loyalty. To determine the purpose of this study, data were collected from the total population using questionnaire gform as many as 100 randomly selected respondent in Surakarta residents. Data was collected through a well-developed structured questionnaire. The influence of celebrity endorsements was calculated using the Smart Partisl Least Squares (SmartPLS) tool. The result show that celebrity endorsement attracts consumer attention and the product will get easily recognized because of the artist, especially when the product includes photocard of the artist. Research could be conducted with a larger number of respondents with diverse characteristics.